(untitled) (Journal of Pharmaceutical Negative Results, 2023)
As antibiotic resistance is increasing day by day, there is a need to develop alternative sources. Being a natural source, Cinnamomum verum and Amomum subulatum can be considered as an alternative therapy. The aim of the current study was to isolate E. coli and Shigella from Urinary tract infected Patients and evaluating the antimicrobial potential of the Cinnamomum verum, Amomum subulatum and antibiotics both synergistically and antagonistically. A total of 50 urine samples were collected from Patients admitted in Khyber Teaching Hospital, and processed using standard gram staining and biochemical test procedures. Furthermore, extract of Cinnamomum verum and Amomum subulatum were made using standard protocol. Agar well diffusion method was used for the evaluation of antibacterial activity. Two bacteria were isolated i.e. E. coli (74%) and Shigella (26%). A total of 02 antibiotics were used in the current study i.e. Ciprofloxacin and Cefixime. Ciprofloxain showed highest zone against E. coli (27 mm) followed by Shigella (20 mm) whereas Cefixime showed (25 mm) zone against E. coli. Amomum subulatum showed highest zone against E. coli (23 mm) whereas Cinnamomum verum showed potent activity against Shigella (17 mm) followed by E. coli (14 mm). When the Cinnamomum verum and Amomum subulatum were used in combination with the antibiotics, it was noticed that the highest activity was shown by Amomum subulatum with Cefixime (32 mm) whereas (30 mm) zone of inhibition was calculated when Cinnamomum verum was used in combination with Ciprofloxacin against E. coli. It is concluded from the present research study that the use of appropriate antibiotics in combination with Cinnamomum verum and Amomum subulatum extract are very essential to reduce the level of antimicrobial resistant and also very important in treating several types of microbial infection because of its antimicrobial activities.